Factors influencing the cytotoxicity of α-methylene-γ-hydroxy esters against pancreatic cancer. Issue 19 (1st October 2015) - Ramachandran, P. Veeraraghavan; Helppi, Matthew A.; Lehmkuhler, Arlie L.; Marchi, Jennifer M.; Schmidt, C. Max; Yip-Schneider, Michele T.
Graphical abstract